Protocol for the development of the international population registry for aphasia after stroke (I-PRAISE). Issue 4 (3rd April 2022) - Ali, M; Ben Basat, A Lifshitz; Berthier, M; Blom Johansson, M; Breitenstein, C; Cadilhac, D A; Constantinidou, F; Cruice, M; Davila, G; Gandolfi, M; Gil, M; Grima, R; et al.
ABSTRACT: Background: We require high-quality information on the current burden, the types of therapy and resources available, methods of delivery, care pathways and long-term outcomes for people with aphasia. Aim: To document and inform international delivery of post-stroke aphasia treatment, to optimise recovery and reintegration of people with aphasia. Methods & Procedures: Multi-centre, prospective, non-randomised, open study, employing blinded outcome assessment, where appropriate, including people with post-stroke aphasia, able to attend for 30 minutes during the initial language assessment, at first contact with a speech and language therapist for assessment of aphasia at participating sites. There is no study-mandated intervention. Assessments will occur at baseline (first contact with a speech and language therapist for aphasia assessment), discharge from Speech and Language Therapy (SLT), 6 and 12-months post-stroke. Our primary outcome is changed from baseline in the Amsterdam Nijmegen Everyday Language Test (ANELT/Scenario Test for participants with severe verbal impairments) at 12-months post-stroke. Secondary outcomes at 6 and 12 months include the Therapy Outcome Measure (TOMS), Subjective Index of Physical and Social Outcome (SIPSO), Aphasia Severity Rating Scale (ASRS), Western Aphasia Battery Aphasia Quotient (WAB-AQ), stroke and aphasia quality of life scale (SAQoL-39), European Quality of Life Scale (EQ-5D), lesion description, General Health Questionnaire (GHQ-12), resource use, and satisfaction with therapy provision and success. We will collect demography, clinical data, and therapy content. Routine neuroimaging and medication administration records will be accessed where possible; imaging will be pseudonymised and transferred to a central reading centre. Data will be collected in a central registry. We will describe demography, stroke and aphasia profiles and therapies available. International individual participant data (IPD) meta-analyses will examine treatment responder rates based on minimal detectable change & clinically important changes from baseline for primary and secondary outcomes at 6 and 12 months. Multivariable meta-analyses will examine associations between demography, therapy, medication use and outcomes, considering service characteristics. Where feasible, costs associated with treatment will be reported. Where available, we will detail brain lesion size and site, and examine correlations with SLT and language outcome at 12 months. Conclusion: International differences in care, resource utilisation and outcomes will highlight avenues for further aphasia research, promote knowledge sharing and optimise aphasia rehabilitation delivery. IPD meta-analyses will enhance and expand understanding, identifying cost-effective and promising approaches to optimise rehabilitation to benefit people with aphasia.